Radical-induced, proton-transfer-driven fragmentations in [b5 − H]˙+ ions derived from pentaalanyl tryptophan1. Issue 16 (28th April 2015) - Williams, Declan; Lau, Justin Kai-Chi; Zhao, Junfang; Mädler, Stefanie; Wang, Yating; Saminathan, Irine S.; Hopkinson, Alan C.; Siu, K. W. Michael
<x xml:space="preserve">Abstract</x> Dissociation of [b5 − H]˙+ ions show sequence scrambling with the Trp residue and radical centre always retained in the product ions.